+0  
 
0
107
3
avatar

The polynomial P(x) satisfies P(x + 2) - P(x) = 6 and P(0) = 2.  Find P(x).

 Dec 13, 2019
 #1
avatar+21725 
0

When x = 0    p(0) = 2

p(0+2)-p(0) =6

p(2)-2= 6

p(2)=8

 

p(2+2) -p(2)=6

p(4)=14

 

I think p(x) = 3x+2   ??

 Dec 13, 2019
 #2
avatar+108626 
+2

EP is correct.

 

I used the same method as EP and found

 

x -2024
P(x) -4 2 814

 

As x increases by 2,   P(x) increases by 6

This is a linear relationship, hence it will be a line.   

The gradient will be  6/2 = 3

The y intercept is 2

so

the line is

P(x)=3x+2

 Dec 13, 2019
edited by Melody  Dec 13, 2019
 #3
avatar+109064 
+1

THX, EP  and Melody.....!!!!

 

 

cool cool cool

CPhill  Dec 13, 2019

19 Online Users

avatar